Alur Pelayanan Pemesanan, Pengolahan, dan Pendistribusian Salad Detox pada Kitchen di PT Bangsus Sukses Bersama Surabaya - Aluna Sagita Nareswari; Niken Purwidiani; Any Sutiadiningsih; Ila Huda Puspita Dewi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The research objective of this final assignment is to describe the service flow for ordering, processing and distributing detox salad food sold at PT Bangsus Sukses Bersama Surabaya. This research uses theories from experts who discuss ordering flow, processing flow, and distribution flow. This theory uses qualitative methods with a descriptive approach. Data collection techniques used were interviews and documentation. The research focus of this final assignment is the ordering service flow, processing flow and distribution flow at PT Bangsus Sekses Bersama Surabaya. The results of the final project research show that PT Bangsus Sukses Bersama Surabaya has provided the best ordering service flow to customers. PT Bangsus Sukses Bersama creates processing flows that comply with operational standards set by the management team of PT Bangsus Sukses Bersama Surabaya. On the other hand, the distribution flow for detox salads implemented by PT Bangsus Sukses Bersama always maintains customer trust by providing the best service and improving the quality of detox salads.